The intestinal microbiota of patients with type 2 diabetes is associated with the C-512T polymorphism of the FOXC2 gene - Liang, Lei; Zhou, Hongjiang; Zhang, Xuxiang; Su, Yandan; Zhao, Ying; Nian, Xin (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the correlation between the C-512T polymorphism of the FOXC2 gene and intestinal microbiota in patients with T2DM.MethodsPeripheral blood and fecal specimens were collected from 170 patients with T2DM and tested for the C-512T polymorphism of the FOXC2 gene by DNA sequencing. Based on the genotype test results, 120 patients were finally included and divided into CC, CT, and TT groups (40 patients in each group). The structural composition and function of the intestinal microbiota were analyzed using 16S rRNA gene sequencing, and differences between groups of intestinal microbiota were assessed.ResultsAlpha Diversity analysis suggested that there was no prominent difference in the abundance and diversity of intestinal microbiota among CC, CT, and TT groups. PCoA analysis in Beta diversity suggested that the composition of enteric flora might be different between CC and CT groups (P = 0.006078, P < 0.05); Anosim analysis showed that the differences in the structure of the intestinal microbiota were greater among the three groups than within the groups (R = 0.02203, P = 0.035, P < 0.05), with the greatest variability in the CC and TT groups. Finally, LefSe analysis revealed that Coriobacteriia, Clostridiales, Clostridiaceae, and Collinsella were significantly more abundant in the CC group than in the TT group.ConclusionThe C-512T polymorphism in the FOXC2 gene has been associated with the structural abundance and species composition of type 2 diabetic intestinal microbiota.